Prevalence of hearing loss in patients visiting ENT OPD of Nepal APF Hospital - Dhungana, Sundar; Maharjan, Alisha; Maharjan, Leison (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Hearing loss (HL) is one of the major health concerns worldwide and is said to be present in a person who has a hearing threshold of more than 20 dB in one or both ears. This study aimed to find the prevalence and its different types and grades of hearing loss in adult patients visiting ENT OPD of Nepal APF Hospital. Method: This is a retrospective cross-sectional study which reviews the data of the patients visiting ENT outpatient department of Nepal APF Hospital from April 15, 2020 to April 14, 2022. Ethical clearance was taken from the Nepal Health Research Council; Ref. No. 1109/2024. The total number of patients vis-iting ENT OPD during the study duration with age group more than 15 years of age was included for the study. Result: Out of 3201 adult patients visited the ENT OPD over two years, 1697(53%) were and 1504(47%) were female, 148 were found to have hearing loss in one or both ears. Thus the prevalence in the adult population in this study group was found to be 4.62%. The prevalence was found to be higher in males 89(5.24%) than in female 59(3.92% ) and also higher in the conductive type of hearing loss 68(2.12%). Conclusion: Hearing loss is the one of the commonest presentation in ENT OPD. The prevalence of hearing loss found is 4.62% which is slightly lower than the previous similar studies. The commonest type of hearing loss is Conductive hearing loss with male predominance